2020
DOI: 10.2337/figshare.12059250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood pressure variability and risk of heart failure in ACCORD and the VADT

Abstract: Objective: Although blood pressure variability is increasingly appreciated as a risk factor for cardiovascular disease, its relationship with heart failure is less clear. We examined the relationship between blood pressure variability and risk of heart failure (HF) in two cohorts of type 2 diabetes participating in trials of glucose and/or other risk factor management. <p> </p> <p>Research Design and Methods: Data were drawn from the Action to Control Cardiovascular Risk in Diabetes (ACCORD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 0 publications
4
13
1
Order By: Relevance
“…Recent studies demonstrated that cardiovascular events, as well as TOD, are associated with the degree of BPV independent of blood pressure levels, 2–10 which seems to be incompatible with the present results, though some investigators have not observed such an association 27–29 . However, most studies investigating the clinical significance of BPV have targeted various patient populations.…”
Section: Discussioncontrasting
confidence: 92%
“…Recent studies demonstrated that cardiovascular events, as well as TOD, are associated with the degree of BPV independent of blood pressure levels, 2–10 which seems to be incompatible with the present results, though some investigators have not observed such an association 27–29 . However, most studies investigating the clinical significance of BPV have targeted various patient populations.…”
Section: Discussioncontrasting
confidence: 92%
“…Moreover, we provide an assessment of this association across a wide spectrum of baseline blood pressure, leading to the identification of stronger relationships with mortality in those with high or low blood pressure, and in particular with cardiovascular death. These data support the notion that the nonlinear influences of BPv on risk of cardiovascular outcomes reported by us 7,12 and others may extend to fatal endpoints.…”
Section: Discussionsupporting
confidence: 89%
“…3 In patients with established coronary heart disease from the STABIL-ITY trial, a robust risk of the major adverse cardiovascular event outcome (P = 0.008) due to BPv was noted in those with low levels of diastolic function (<67 mmHg). 5 Our own prior analyses using the ACCORD trial revealed several interesting findings: heart failure risk due to BPv increased only in lower categories of baseline blood pressure, 12 while for coronary heart disease and the primary CVD outcome, BPv indicated risk exclusively in both high and low strata of blood pressure. 7 The present analysis highlights for the first time the relevance of ambient blood pressure when considering the potential impact of BPv on mortality in a purely diabetes cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, emerging evidence suggested that the longterm variability of many risk factors, including blood pressure [3,5], lipids [6,7], and glycosylated hemoglobin (HbA1c) [8,9], were associated with adverse cardiovascular outcomes and mortality. These effects remained significant after adjusting for the mean levels of the parameters, suggesting that not only managing the absolute value but also reducing the fluctuation should be targeted to improve health outcomes.…”
Section: Introductionmentioning
confidence: 99%